KOMBINASI PENAMBAHAN SHIELDING TIMBAL MESIN FLUOROSCOPY BAGASI DAN PENGATURAN JARAK PEKERJA TERHADAP SUMBER RADIASI MENURUNKAN PAPARAN RADIASI SINAR X DAN KELELAHAN MATA PADA PEKERJA SCREENING DI BANDARA INTERNASIONAL X - Iffah, Maghfirotul; Adiatmika, I Putu Gede; Adnyana, I Wayan Bandem; Sutjana, I Dewa Putu; Muliarta, I Made; Swamardika, Ida Bagus Alit (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic); Vol 4 No 1 (2018): Volume 4 No 1 Juni 2018DO - 10.24843/JEI.2018.v04.i01.p01, 2018)
Screening is ordinary process airport passanger was machine baggage. X-ray radiation gives impact to eye because eye sensitive of radiation. Many kinds of eye strain symptom got by screening worker such eye poignant. It is neressary to give  intervention to decrease the radiation exposure and eye strain for worker by increasing lead shielding on the fluoroscopy machine baggage and setting of worker distance toward the source of radiation.             Experimental research with pre-post test control group design. A sampel of 30 people were taken with a simple randomized method which was subdivided into group 1 as a control group without the additional treatment of lead shielding and working distance regulation of the radiation source, group 2 with the addition of a shielding and setting distance as far as 2 m. the study was conducted in August 2017. The variables evaluated were exposure to the received radiation of workes and the strain of the workers eyes.             The result of the research is a combination of  lead shielding on machine baggage fluoroscopy and setting of working distance to X ray source at X International Ariport significantly (p<0,05) in decreasing radiation exposure received by worker equal to 74,59% and worker eye strain 68,85% for a distance of 1,5 m and decreased radiation exposure to the workers as much as 93, 69% and the eye strain on the worker 89,79% at a distance of 2 m from the radiation source.             Concluded that the combination of increasing lead shielding and the setting of worker distance toward the source of radiation decrease thr radiation exposure and eye strain on the screening worker at X International airport.